Estudio de las prácticas de responsabilidad social de los canales de televisión de la ciudad de Loja: Ecotel Tv, Uv Televisión, Canal Sur y Plus Tv, frente a la mitigación y adaptación del cambio climático en el año 2019 - Jefferson Alejandro Collaguazo Balcázar, Jefferson Alejandro (2020)
Climate change is a global problem, which encapsulates a series of setbacks that directly involve the human being, becoming a problem that affects and is related to multiple perspectives, with the aim of taking actions that contribute to the deterioration of our planet. In this context, this research was born, to determine and analyze the role of television channels in the city of Loja against climate change in 2019. To do this, a mixed approach methodology was used, divided into four stages where implemented various techniques such as: direct observation, with the help of charts to determine the responsibility practices of each channel; the in-depth interview with managers of each channel to determine environmentally responsible practices; content analysis to determine the contribution of television channels in the city of Loja to climate change; and finally, for the second time, the in-depth interview addressed to experts to create an alternative proposal that would make it possible to contribute to the work of the television media in favor of solving the problem addressed in the research. The results made it possible to identify and contrast the practices of responsibility of television channels with regard to the mitigation and adaptation of climate change.